2014
DOI: 10.3390/min4010037
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Treatment of Mercury Mine Wastes Using a Rotary Solar Kiln

Abstract: Thermal desorption, by a rotary kiln of mercury contaminated soil and mine wastes, has been used in order to volatilize mercury from the contaminated medium. Solar thermal desorption is an innovative treatment that uses solar energy to increase the volatility of contaminants, which are removed from a solid matrix by a controlled air flow system. Samples of soils and mine wastes used in the experiments were collected in the abandoned Valle del Azogue mine (SE, Spain), where a complex ore, composed mainly of cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Navarro et al (2014) confirmed the effectiveness of thermal desorption for the removal of Hg (removal efficiency = 99 %) from a soil collected from abandoned mining area of Iberian Peninsula. Solar thermal desorption could be an innovative AMLs treatment option; however, future studies are warranted in this direction.…”
Section: Other Approaches For Reclamation Of Amlssupporting
confidence: 79%
“…Navarro et al (2014) confirmed the effectiveness of thermal desorption for the removal of Hg (removal efficiency = 99 %) from a soil collected from abandoned mining area of Iberian Peninsula. Solar thermal desorption could be an innovative AMLs treatment option; however, future studies are warranted in this direction.…”
Section: Other Approaches For Reclamation Of Amlssupporting
confidence: 79%
“…There are previous preliminary studies that have demonstrated the viability of the Hg release at temperatures between 127 and 600°C (Chang and Yen 2006;Chang et al 2009;Matsuyama et al 1999;Navarro et al 2009Navarro et al , 2014Palmieri et al 2006). Hg will be released at different temperatures depending on the phase to which it is linked (Navarro et al 2009(Navarro et al , 2014. Studies about the remediation of Hg-polluted soils by thermal desorption at low temperature have shown Hg removal of over 99 % in sand matrices (Kunkel et al 2006); negligible values in mining soils and residues which have a great percentage of pyrite and cinnabar in their composition; 76 % in mining soils and residues which have the most of Hg from atmospheric deposition (Navarro et al 2009); and the thermal treatment of an Hg-contaminated soil (69 mg kg −1 ) with a common chloridizing agent (FeCl 3 ) at a reduced temperature (400°C) reduced to a level below the maximum mercury concentration allowed for soil in China (Fujun et al 2014).…”
Section: Introductionmentioning
confidence: 91%
“…A typical thermal desorption unit for Hg removal operates at temperatures from 320 to 700°C (United States Environmental Protection Agency (US EPA) 2007), and it is one of the few methods that are effective for very high Hg concentrations (Xu et al 2015). There are previous preliminary studies that have demonstrated the viability of the Hg release at temperatures between 127 and 600°C (Chang and Yen 2006;Chang et al 2009;Matsuyama et al 1999;Navarro et al 2009Navarro et al , 2014Palmieri et al 2006). Hg will be released at different temperatures depending on the phase to which it is linked (Navarro et al 2009(Navarro et al , 2014.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The use of thermal desorption to volatilize Hg from Hg-contaminated soil and mine wastes is described by Navarro et al [15], and Mäkitalo et al [16] outline the properties of green liquor dregs (GLD), alkaline residual materials produced by sulfate paper mills. Johnson [17] reviews recent advances in biotechnologies using microorganisms that can reduce the reactivity of potentially hazardous mine tailings and selectively remove metals and other contaminants from mine waters.…”
mentioning
confidence: 99%